Using saline solutions for ACE washouts. Issue 2 (19th September 2007) - Hyde, S-J; Coulthard, M G; Jaffray, B; Vallely, M E; Harding, S M
Abstract : We had found that twice-normal saline (2NS) antegrade continence enema (ACE) lavages were better than with normal saline (NS) but caused unpleasant symptoms. We therefore undertook a double-blind crossover study comparing water, NS and 2NS in four children. NS produced no disturbances, but water caused a transient fall in plasma osmolality of 7.3 mosmol/kg at 20 min, and falls in urine sodium and osmolality. With 2NS, the plasma sodium rose by 2.5 mmol/l, the plasma proteins rose by 2.3 g/l and the lavage fluid sodium fell, suggesting that about 10 ml/kg of plasma water had moved into the colonic lumen, and two subjects became thirsty. Five other children did home testing. Their home-produced saline was too concentrated and varied widely, and they found that 30 ml/kg of NS produced the same washout result as 20 ml/kg of 2NS. Carefully made-up NS should be used for lavage, increasing volumes if necessary.